Faktor-Faktor yang Mempengaruhi Kepuasan Pelanggan pada UD Pandan Wangi Semarang - Aditia, Indra; ., Suhaji (Jurnal Kajian Akuntansi dan Bisnis, 2012)
This study aimed to determine the factors that influenced customer satisfaction atUD. Pandan Wangi. This study used the subject data. In this case the subject of the research wasthe UD. Pandan Wangi customers. This study used the method of sample selection ofnonprobability sampling. with purpose sampling, especially consideration (judjement sampling)which means that the type of sample selection was not random of which the information wasobtained by using a certain consideration that mean the respondent had made a purchaseminimum of three times. The number of samples was taken as many as 100 people. The dataanalysis technique was multiple linear regression. The result showed that the quality of theproduct didnât influence the customer satisfaction rates, price didnât influence the customersatisfaction, service quality influenced customer satisfaction, emotional factor didnât influencethe customer satisfaction, the cost and ease influenced the customer satisfaction. Whilesimultaneously the product quality, price, service quality, emotional factor, and the cost and easeinfluenced customer satisfaction.Keywords: product quality, price, service quality, emotional factor, the cost and easePENDAHULUAN